PENGEMBANGAN GASTRONOMY GARDEN SEBAGAI WISATA EDUKASI DI DESA TARO KABUPATEN GIANYAR BALI - Darma Susila, I Made Gede; Anggreni Suryaningsih, Ida Ayu; Guntur Pramana Putra, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024), 2025)
With the development of new tourism will be able to increase the interest of tourists to visit Taro Village. The development of Gastronomy Garden is more to the concept of educational tourism development and tourism activities. The purpose of this study was to identify the tourism potential of tourist attractions in Gastronomy Garden and the potential development of educational tourism in Taro Tourism Village. This research is in the form of primary data in this research in the form of field observation results, while secondary data in the form of location description data and and the history of the formation of these tourist attractions. Data collection in this study using observation, interviews and literature studies with analyzed with descriptive qualitative. The results of this study indicate the potential of educational tourism that can be developed in the gastronomy garden. The potential is seen from cognitive, affective and behavioral aspects. Cognitive aspects can be seen through the procedures for planting plants used as food ingredients, caring for plants, choosing plants used and procedures for processing food ingredients. From the affective aspect, it can be seen about the attitude and way of thinking of the community, which includes the procedures for selecting and using plants. Then from the behavioral aspect regarding skills in processing food. Therefore, it is important for tourism stakeholders to develop this educational tourism. This is so that it can provide educational value to tourists who visit and can maintain this tour in a sustainable manner.